Racially and Ethnically Diverse Women Leading Education : a World View. - Normore, Anthony H. (Advances in educational administration., 2016)
This book's primary focus is on racially and ethnically diverse women in educational leadership. Each chapter is written from a unique conceptual or empirical lens as shared by international female leaders, and range from a critical examination of global society and cross-cultural collaboration, to the intersection of race, law, and power.